Postmortem Aviation Forensic Toxicology: An Overview - Chaturvedi, Arvind K. (Journal of analytical toxicology, 2010)
An overview of the subtopic aviation combustion toxicology of the field of aerospace toxicology has been published. In a continuation of the overview, the findings associated with postmortem aviation forensic toxicology are being summarized in the present overview. A literature search for the period of 1960–2007 was performed. The important findings related to postmortem toxicology were evaluated. In addition to a brief introduction, this overview is divided into the sections of analytical methods; carboxyhemoglobin and blood cyanide ion; ethanol; drugs; result interpretation; glucose and hemoglobin A1c; and references. Specific details of the subject matter were discussed. It is anticipated that this overview will be an outline source for aviation forensic toxicology within the field of aerospace toxicology.